Identification and validation of low-inference measures of teaching effectiveness at the tertiary level - Agbisit, Clarita F. (Clarita Felix)
The aim of the study is to identify teaching behaviors that can be used as indicators of teaching effectiveness at the tertiary level of education. The framework of the study rests on the theory that effective teachers perform in certain ways that distinguish them from ineffective teachers, and students are in the most disadvantageous position to determine what these behaviors are. The contribution of the paper to the improvement of education is in the development of more valid measures of teaching effectiveness that will be useful to teacher educators, supervisors, students, and teachers themselves.